Close range photogrammetry and machine vision - Atkinson, Keith B. (Whittles Pub., 1996)
Annotation Over the past decade, advances in the field of close-range photogrammetry have been rapid and the era of digital photogrammetry is well on its way. This book provides a complete account of the subject with contributions from international experts.
Keywords: Photogrammetry.; Computer vision.; Image processing -- Digital techniques.; elektronické knihy; electronic books